DEVELOPMENT OF AN INTERPROFESSIONAL GERIATRICS TEACHING CLINIC FOR COMPREHENSIVE CLINICAL EDUCATION AND CARE. (11th November 2018) - Halli-Tierney, A; Carroll, D; McKinney, R; Allen, R
Abstract: An interprofessional geriatric clinic was established with the purpose of teaching family medicine residents to provide geriatric patient care and to learn how to participate as a member of an interprofessional team. The model was recognized as a novel, real-time means of providing education on both geriatric clinical care and interprofessional collaboration, and learners from other disciplines were added for co-educational purposes. Within the clinic five professions (medicine, psychology, social work, nursing, pharmacy) practice together to provide direct patient care; learners are currently present from four (medicine, psychology, social work, pharmacy). We will describe the planning and establishment of this clinic, interprofessional learning gained from the experience, and challenges of implementing an interprofessional educational experience within a functioning primary care clinic. Interprofessional learning is emerging as a vital means of postgraduate training, as the medical field (among others) moves toward collaboration as comprehensive care model. Interprofessional education is a relatively new field; the development, implementation, impact, and outcomes (learners' subsequent careers and continued interprofessional collaboration) of such educational experiences have not been clearly examined. Most published literature regarding interprofessional education involves only two health care professions and is associated within a formal classroom or simulation setting; not from real world patient care. Our geriatric clinic is unique since five professions work together to provide direct patient care while in clinic. The goal is to train healthcare providers from multiple professions to provide compassionate, competent care to older patients through collaborative training, and to actively improve the health of the community.